Flexible matter: A real-time shape exploration employing analogue and digital form-finding of tensile structures. (December 2016) - Symeonidou, Ioanna
The article presents a research on real-time shape exploration employing analogue and digital form-finding and concludes with a proposal for a teaching methodology that led to an intensive student workshop which took place at the Institute of Architecture and Media at Graz University of Technology. The aim was to experiment with analogue and digital tools in parallel, counter-informing the design process. The experiments involved physical form-finding following the tradition of Frei Otto at the Institute of Lightweight Structures in Stuttgart as well as computational form-finding employing mainly dynamic relaxation techniques of spring-particle systems. The combination of techniques and methodologies eventually led to a feedback loop across different media that explored both qualitative and quantitative characteristics of the projects at hand. By establishing feedback between digital media and physical prototypes, the creative process is immediately informed by the material characteristics and properties which in turn give rise to a real-time exploration of form. Simulations of physical forces for architectural form generation are increasingly gaining ground in architectural education as there is a broad selection of computational tools readily available that allow quick experiments to be conducted.